Agaricus santacatalinensis a new species from Argentina - Albertó, E. (1998)
A. santacatalinensis, found in exotic broadleaf woods in the environs of Buenos Aires, is described and illustrated. It belongs to subgenus Lanagaricus and is characterized by the chamois-like to velvety aspect of the pileus, the ochraceous yellowish color of the stipe with orange hues and detersile fibrils, and the centrifugally maturing process of the lamellae. A key to Argentinian species of the subgenus is proposed.